2023
DOI: 10.1111/jpi.12892
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic crosstalk among gut microbiome, hypothalamic and hepatic circadian clock oscillations, immunity and metabolism in response to different light–dark cycles: A multiomics study

Yongkang Zhen,
Yifan Wang,
Feiyang He
et al.

Abstract: The accelerated pace of life at present time has resulted in tremendous alterations in living patterns. Changes in diet and eating patterns, in particular, coupled with irregular light–dark (LD) cycles will further induce circadian misalignment and lead to disease. Emerging data has highlighted the regulatory effects of diet and eating patterns on the host‐microbe interactions with the circadian clock (CC), immunity, and metabolism. Herein, we studied how LD cycles regulate the homeostatic crosstalk among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 104 publications
(229 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the study demonstrated that GM could influence immune and metabolic disorders caused by circadian dysregulation. These insights offer potential targets for developing probiotics specifically tailored for individuals with circadian disruption, such as shift workers ( Zhen et al 2023 ).…”
Section: Two Inseparable Ropes: Circadian Rhythms and The Gmmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study demonstrated that GM could influence immune and metabolic disorders caused by circadian dysregulation. These insights offer potential targets for developing probiotics specifically tailored for individuals with circadian disruption, such as shift workers ( Zhen et al 2023 ).…”
Section: Two Inseparable Ropes: Circadian Rhythms and The Gmmentioning
confidence: 99%
“…In the study conducted by Zhen et al (2023), the researchers explored the impact of different LD cycles (LD light hour/dark hour) on the interconnected rhythms of GM, hypothalamic, and hepatic clock genes, as well as immunity and metabolism. They employed multi-omics approaches to investigate four irregular LD cycles (LD0/24, LD24/0, LD8/16, LD16/8) along with a normal LD cycle (LD12/12).…”
Section: Two Inseparable Ropes: Circadian Rhythms and The Gmmentioning
confidence: 99%
“…However, previous studies and our recent studies have shown that the mechanism of probiotic intervention on host physiology is extremely complex, and the gut microbiome enhances intestinal health by playing a direct or indirect regulatory role [10,12,[19][20][21]. These regulatory mechanisms involve complex systems to control various aspects of intestinal homeostasis (intestinal barrier function and immune regulation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These microbial diurnal rhythms synchronize with feeding rhythms to anticipate host gut function and can be affected by dietary nutrients [14,16]. Circadian transcription factor NFIL3, histone deacetylase, gut-microbe-generated short-chain fatty acids, and rhythmic hormone melatonin were recruited rhythmically, and produced synchronized diurnal oscillations in histone acetylation, metabolic gene expression, and nutrient uptake [17][18][19][20]. Choi et al systemically reviewed microbial oscillators that are generally promoted by dietary nutrients, such as plant-based, low-fat (lean) diets, and most were abolished by low-fiber, high-sugar, high-fat (Western) diets [16].…”
Section: Introductionmentioning
confidence: 99%